The Effect of Using Flashcard on Students’ Vocabulary at Ninth Grade of SMP Negeri 6 Kota Jambi in academic 2018/2019 - Dina Alpiana; Wennyta Wennyta (Universitas Batanghari Jambi, 2020)
The purpose of this research is to find out whether, there is a significant effect of teaching using flashcard on students’ vocabulary at ninth grade of SMP N 6 Kota Jambi in academic year 2018/2019. The research specifically is to find out whether the flashcard effectively increases the students’ vocabulary (verb). The research method used in this study was a quali- experimental study. The samples were class 9E as experimental class and class 9C as control class taken from the ninth grade students of SMP N 6 Kota Jambi by using cluster sampling techniques. The experimental class was taught by using flashcards while the control class was taught without using flashcards. Both classes were given pre-test and post-test. Pre-test and post-test consisted of 25 essay questions. The collected data in this research were analyzed by using t-test. The result of data analysis showed of the t-test between control class and experimental class. The findings displayed that the value of t-test is 58.066/. for control class and 67.082 for experimental class and sig. (2 tailed) = . 000, whereas the value of t-table with the degree of freedom 35 ( df=36-1 ) and the level of the significance 0.05 are 1.689. Therefore, the null hypothesis (Hₒ) was rejected and alternative hypothesis (Hₐ) was accepted. There was significant difference between students’ vocabulary achievement by using flashcards and without flashcards. Thus, it could be concluded that the teaching vocabulary using flashcards was effective on students’ vocabulary achievement (verb). It means that the effect of using flashcard on students’ vocabulary at ninth grade of SMP N 6 Jambi City in academic year 2018/2019 was accepted.Keywords: Vocabulary, Teaching Vocabulary, Flashcards.